Analisis Cost Volume Profit (CVP) Sebagai Alat Perencanaan Laba pada UMKM Ayam Broiler Ibu Ramlah - Iksan Hikmatullah; Fajar Dini Harianto; Muhammad Riyanto Gufron; Mohamad Bastomi (Yayasan Literasi Sains Indonesia, 2023)
A successful business venture requires careful planning in terms of sales and expenses in order to generate profit. To achieve optimal profits, entrepreneurs must use Cost Volume Profit (CVP) analysis. Mrs. Ramlah's broiler chicken business has never conducted CVP analysis, resulting in less than maximum profits. This research aims to examine CVP analysis in Mrs. Ramlah's broiler chicken business. The method used is qualitative descriptive with a case study approach. The researcher obtains data through direct interviews with Mrs. Ramlah and then conducts data analysis. CVP analysis is conducted using Break-Even Point, Contribution Margin, Margin of Safety, and Degree of Operating Leverage. The research results of 2022 show that the BEP (units) must sell 2,700 and the BEP (rupiah) must earn 161,192,307 to avoid losses. The Contribution Margin ratio is 13%, the Margin of Safety in rupiah can drop up to 933,807,693 and Degree of Operating Leverage shows that Contribution Margin is 1.17 times the operating profit.